Snippets of India2019;s Polar Research (Global Journal of Human-Social Science, 2021)
Distant non Arctic states non government organisations international organisations etc have evinced interest and staked claim for engagement in the Arctic Council and thus Arctic has become a geopolitical geo-economic issue of great importance in the recent times India has cited climate change as well as impact and inter-connection between the Arctic climate and Indian monsoons due to the receding ice cover as a basis of its research thus legitimising its role as an Observer and stakeholder Despite the huge geographical distances between India and the Poles it possesses an exceptional alpine region with the Himalayas in its background having polar characteristics to aid polar scientific research